Perioperative Outcomes of Postmenopausal Women with Colorectal Cancer Undergoing Prophylactic Salpingo-oophorectomy - Schoenmaker, Eveline M.; van Zon, Jasper F. J. A.; Heijmans, Margot H. M.; Bloemen, Johanne G.; Lettinga, Tanja; de Waard, Jan-Willem D.; Roumen, Rudi M. H. (South Asian Journal of Cancer, 2025)
Women with colorectal cancer have an increased risk of developing ovarian malignancies, which have a poor prognosis. Shared decision making on the possibility of prophylactic salpingo-oophorectomy (PSO) during colorectal cancer surgery in postmenopausal women has, therefore, been implemented. Effects of PSO on perioperative parameters are unknown. This study therefore compares perioperative parameters between women with and without PSO.Women undergoing colorectal cancer surgery between January 2020 and March 2023 in four centers in the Netherlands offering the possibility of PSO were included. Perioperative parameters were compared between the group with and without PSO.Continuous data were analyzed with independent t-tests or nonparametric tests when applicable. Categorical variables were analyzed with chi-square tests. Propensity score matching was performed to control for potential confounders. The variables age, American Society of Anesthesiologists classification, TNM stages, and type of surgery were used as respective covariates. Perioperative data were again analyzed between the matched groups. A sensitivity analysis including all participants was performed to evaluate the effect of PSO on duration of admission and on complications.The present study included 112 women who underwent PSO and 28 who did not. The PSO group was significantly younger (median: 74 vs. 79 years, p = 0.002), had a shorter hospital stay (median: 4 vs. 6 days, p = 0.006), and experienced less overall postsurgical complications (31 vs. 64%, p = 0.002). These differences were neither observed after propensity score matching nor after sensitivity analysis. Malignant adnexal tissue was identified in three patients.PSO in combination with elective colorectal cancer surgery in postmenopausal women does not lead to different or worse perioperative outcomes compared with the group without PSO. Nonetheless, the decision to undergo this combined surgery should be made on individual basis. Future research needs to focus on long-term follow-up and generalizability.
Keywords: prophylactic salpingo-oophorectomy; shared decision making; ovarian malignancies; colorectal cancer; surgical outcomes